Evaluating haze formation in flavoured lager beers using a range of forcing methods. Issue 3 (6th July 2017) - Rice, Christopher J.; Pawlowsky, Karin; Smart, Chris
Abstract : Haze formation is a quality problem that can affect a wide range of drinks for a number of different reasons. Although well‐characterized in traditional beers, the emergence of novel beer‐based beverages has led to the potential for chemical interactions that can result in the precipitation of haze material. In this study, the haze formation in 19 commercially available flavoured lager beers was investigated. The chemical parameters of each of the drinks were measured and haze formation was induced through three forcing tests, developed for use in both the beer and wine industries, as well as using a novel forcing test, designed for this study. Several of the products were particularly susceptible to a number of haze forcing tests and the EBC temperature cycling and the Wine Forcing (70°C) tests were found to generate the most forced haze (measured at 90 and 13° scatter angles, respectively) in these products. There was no overall correlation between the drinks' chemical parameters and their susceptibility to haze formation. However, a weak, but statistically significant, correlation ( p = 0.044) was observed between the concentration of polyphenols in the products and the presence of haze measured by 90° scatter angle. Copyright © 2017 The Institute of Brewing & Distilling